Treatment of textile effluents by using natural coagulants. (2020) - Prabhakaran, G.; Manikandan, M.; Boopathi, M.
Highlights: Improvement in quality of textile water by using natural coagulants. Natural coagulant such as nirmali seeds & water hyacinth are used for treatment. Substitute for chemical coagulants leading to sustainability. Cost effective method with less floc formation. Abstract: A brief study on the investigational analysis for the handling of industrial waste water (washing water) had been carried out for the analysis of improved treatment of water by using natural coagulants. While treatment, natural coagulant such as Strychnos potatorum (nirmali seeds), Eirchorrnia crassipes (water hyacinth) are used for waste water treatment. This contains the various parameters such as pH, sulphates, chlorides, total solids, total suspended solids (TSS), total dissolved solids (TDS), acidity, alkalinity, optimal coagulant prescription (jar apparatus), biological oxygen demand (BOD) and chemical oxygen demand (COD). These natural coagulants, when used for treatment of waters with low to medium turbidity range (50–500 NTU), are comparable to their chemical foils in terms of treatment. The test results showed that the natural coagulants provide better results which can be used as either distinctly or in combination with chemical coagulant alum. The natural coagulant produces lesser floc; hence the cost of sludge treatment is reduced. From the natural coagulants used, water hyacinth gives better result than nirmali seed. The natural coagulants can be used for treatment of textile waste wherever it is available in sufficiently.